The Insulin-Like Proteins dILPs-2/5 Determine Diapause Inducibility in Drosophila. - Luca Schiesari; Gabriele Andreatta; Charalambos P Kyriacou; Michael B O'Connor; Rodolfo Costa (PLoS ONE)
Diapause is an actively induced dormancy that has evolved in Metazoa to resist environmental stresses. In temperate regions, many diapausing insects overwinter at low temperatures by blocking embryonic, larval or adult development. Despite its Afro-tropical origin, Drosophila melanogaster migrated to temperate regions of Asia and Europe where females overwinter as adults by arresting gonadal development (reproductive diapause) at temperatures <13°C. Recent work in D. melanogaster has implicated the developmental hormones dILPs-2 and/or dILP3, and dILP5, homologues of vertebrate insulin/insulin-like growth factors (IGFs), in reproductive arrest. However, polymorphisms in timeless (tim) and couch potato (cpo) dramatically affect diapause inducibility and these dILP experiments could not exclude this common genetic variation contributing to the diapause phenotype. Here, we apply an extensive genetic dissection of the insulin signaling pathway which allows us to see both enhancements and reductions in egg development that are independent of tim and cpo variations. We show that a number of manipulations dramatically enhance diapause to ~100%. These include ablating, or reducing the excitability of the insulin-producing cells (IPCs) that express dILPs-2,3,5 employing the dilp2,3,5-/- triple mutant, desensitizing insulin signaling using a chico mutation, or inhibiting dILP2 and 5 in the hemolymph by over-expressing Imaginal Morphogenesis Protein-Late 2 (Imp-L2). In addition, triple mutant dilp2,3,5-/- females maintain high levels of diapause even when temperatures are raised in adulthood to 19°C. However at 22°C, these females all show egg development revealing that the effects are conditional on temperature and not a general female sterility. In contrast, over-expression of dilps-2/5 or enhancing IPC excitability, led to levels of ovarian arrest that approached zero, underscoring dILPs-2 and 5 as key antagonists of diapause.